TRANSFORMASI PEMBELAJARAN IPA KE IPAS DALAM KURIKULUM MERDEKA DI SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Nada Agustin; Anastasia, Sabrina; Adrias (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study ains to eximine the transformation of science learning (IPA) into IPAS (Natural and Social Science) in the implementation of the Merdeka Curriculum in Elementary Schools through a Systematic Literature Review (SLR) approach. Ten relevant scientific journal articles were systematically analyzed using established inclusion and exclusion criteria. The results indicate that the transformation from IPA to IPAS brings significant changes in the learning approach, integrating two disciplines into one holistic subject. Three major themes emerged: (1) implementation challenges, including limited resources, teacher readiness, and diverse conceptual understanding; (2) transformation opportunities, including increased learning motivation, critical thinking development, and strengthened science-social literacy; and (3) effective strategies, including project-based learning (PBL), interdisciplinary approaches, contextual learning, and field trips. The study concludes that the success of IPAS transformation is highly dependent on teacher readiness, infrastructure support, and continuous professional training.